The president and the frog - De Robertis, Carolina (Alfred A. Knopf, 2021)
"From the acclaimed author of Cantoras comes a mystical and heartening tale about seeking justice and the power of memory In his modest home at the edge of town, the former President of a Latin American country receives a journalist in his iconic gardens to discuss his legacy and the dire circumstances that threaten democracy around the globe. Once known as the Poorest President in the World, his reputation is the stuff of myth: a former guerilla who was jailed for inciting revolution before becoming the face of justice, human rights, and selflessness within his nation. And yet, he is tempted to reveal a secret from his past: while he was imprisoned and held in solitary confinement-due to madness or in a surreal twist-he survived in part by conversing with the only creature who ever spoke back, a loud-mouth frog, about revolution, the quest for dignity, and what it means to love a country. As engrossing as it is innovative, The President and the Frog explores the resilience of the human spirit and what is possible when danger looms. Ferrying us between a grim jail cell and lush garden, De Robertis emphasizes that even the smallest voice can change the world. Vivid, heartfelt, and full of wit and humor, The President and the Frog reaches beyond all borders and dares us to be human in the face of chaos"--